2019
DOI: 10.3390/ijms20040949
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the Mechanism of Action of Rapid-Acting Antidepressant Treatment Strategies: Does Gender Matter?

Abstract: Gender differences play a pivotal role in the pathophysiology and treatment of major depressive disorder. This is strongly supported by a mean 2:1 female-male ratio of depression consistently observed throughout studies in developed nations. Considering the urgent need to tailor individualized treatment strategies to fight depression more efficiently, a more precise understanding of gender-specific aspects in the pathophysiology and treatment of depressive disorders is fundamental. However, current treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 115 publications
1
25
0
Order By: Relevance
“…Previous research and results from this study show that estrogen regulation of CYP2B6 gene expression can modulate differential response to ketamine in females (biological sex) ( Figure 5) (92). These results indicate that dose optimization is critically dependent on a patient's endogenous drug profile, biological sex, and age (12,91,92).…”
Section: Genotype-phenotype Annotation Of Different Ketamine Sub-netwsupporting
confidence: 60%
See 1 more Smart Citation
“…Previous research and results from this study show that estrogen regulation of CYP2B6 gene expression can modulate differential response to ketamine in females (biological sex) ( Figure 5) (92). These results indicate that dose optimization is critically dependent on a patient's endogenous drug profile, biological sex, and age (12,91,92).…”
Section: Genotype-phenotype Annotation Of Different Ketamine Sub-netwsupporting
confidence: 60%
“…While exon variants in the CYP2B6 gene may differentially alter splicing but not protein structure or function (89), mutations that alter CYP2B6 mRNA splicing in the human brain contribute significantly to ketamine response variation in humans (90,91). Previous research and results from this study show that estrogen regulation of CYP2B6 gene expression can modulate differential response to ketamine in females (biological sex) ( Figure 5) (92). These results indicate that dose optimization is critically dependent on a patient's endogenous drug profile, biological sex, and age (12,91,92).…”
Section: Genotype-phenotype Annotation Of Different Ketamine Sub-netwmentioning
confidence: 65%
“…Published work so far did not detect a role of gender in the behavioral response to (2R,6R)-HNK administration. Recently, we summarized the evidence of the role of sex in the effects of ketamine and (2R,6R)-HNK [15].The molecular mechanisms of action of ketamine and (2R,6R)-HNK are only partly understood: there are key neurobiological mechanisms that are well-known factors of MDD pathology and therapy, which were found to play a role in the rapid-acting effects of ketamine. For example, a single injection of ketamine activated the mammalian target of rapamycin (mTOR) and this enhanced synaptogenesis in the medial prefrontal cortex (mPFC) [16], reversing the stress-induced synaptic deficits in mice [17].…”
mentioning
confidence: 99%
“…Several studies reported a gender difference in treatment response to antidepressants in mood disorders. 49 In particular, there is some evidence that women respond better to SSRI with respect to men 50,51 (probably due to the interactions between estrogen and serotonin in the brain). 52 When considering PMDD, The Korean Medication Algorithm project for Depressive Disorder, second revision, reported AD monotherapy as the treatment of choice.…”
Section: Antidepressants (Ads)mentioning
confidence: 99%